Development of Combination HIV Prevention Programs for People Who Inject Drugs through Government and Civil Society Collaboration in the Russian Federation. (29th November 2012) - Volik, M. V.; Karmanova, G. A.; Berezina, E. B.; Kresina, T. F.; Sadykova, R. G.; Khalabuda, L. N.; Fattakhov, F. Z.
Abstract : Population Services International (PSI) has worked collaboratively with several government institutions of the Russian Federation to develop and implement a model program to access health services for individuals who are opioid dependent, including those with HIV infection. Through the development of partnership agreements between government organizations (GOs) and non-government organizations (NGOs), a model of the continuum of care has been developed that identifies a Recommended Package of HIV Prevention Services for Injecting Drug Users (RPS-IDU). The implementation of the RPS-IDU in the Russian Federation offers a model for other countries with HIV epidemics associated with injection drug use. This paper will describe the model program and its implementation in one of the pilot program regions.